ANALISIS SEGMENTASI PSIKOGRAFIS DAN TINGKAH LAKU TERHADAP KEPUTUSAN NASABAH UNTUK MENGAMBIL KREDIT PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk. UNIT BATUA RAYA MAKASSAR - Rosnaini Daga (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The purpose of this study is to analyze and determine the effect of psychographic segmentation and behavior on customer decisions to take credit at PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Batua Raya Makassar. The research technique used in this research is using multiple regression analysis by using questionnaire. The population in this study amounted to 1,400 customers, with a sample size of 94 customers. The results of the analysis show that psychographical segmentation (X_1) is 7,414 t with significance level 0.000 where tcount> ttable (7,414> 1,984), this means that psychographic segmentation has a significant positive effect and behavioral Segmentation (X_2) is 6,218 t with significance level 0.000 where tcount> ttable (6.218> 1.984), this means a significant positive effect on the decision of customers to take credit at PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Batua Raya Makassar.